Ten Lessons for a Post-Pandemic World, Fareed Zakaria - Tahir Abbas (CISS Insight Journal, 2024)
“Ten Lessons for a Post-Pandemic World” authored by Fareed Zakaria, an American journalist, political commentator, and an international relations scholar, offers a roadmap for navigating the complex challenges that have emerged in the wake of the global pandemic, predominantly Covid-19. The author brings his intellect and global perspective to the key issues reshaping our world. While examining governance, economics, and culture, this book utilizes a broad lens called “applied history.”With each chapter focusing on a critical aspect of the post-pandemic environment, the book is structured around ten chapters and ten lessons. Through the skillful integration of historical background, geopolitical analysis, and interviews with leading experts, the book provides a thorough analysis of the dynamic forces that will determine the world’s future course. This book is an enticing read, based on the understanding of world affairs, and simplifies complex ideas into readable and captivating narratives.